Systematic genome-wide screens of gene function - Carpenter, Anne E.; Sabatini, David M. (Nature reviews. Genetics, 2004)
Key Points High-throughput screens, in which each gene of an organism is systematically perturbed, are now routine in yeast and are becoming feasible in other organisms. Before conducting a genome-wide screen, the list of gene sequences to be targeted must be compiled and a set of gene-perturbing reagents or strains must be constructed. Gene-perturbing strategies include: homologous recombination and random insertional mutagenesis to delete or mutate genes at the DNA level, and RNA interference to reduce the mRNA levels of a gene. Any observable phenotype can be screened using genome-wide collections of reagents or organisms, subject to practical limitations. Examples of phenotypes that have been screened so far include cell growth and proliferation, classical morphological defects and reporter-gene activity. Using automated microscopy and/or automated image analysis, visual phenotypes can also be screened in a high-throughput manner. Genome-wide phenotypic screens generate large, high-quality data sets, which can be used immediately to identify genes that are involved in a particular process. These genome-wide data sets can also be integrated with existing genome-wide data sets, such as transcriptional profiles and annotated databases, to provide further, broader insights. Future screens will probably examine more complex phenotypes in increasingly physiological contexts. By using genome information to create tools for perturbing gene function, it is now possible to undertake systematic genome-wide functional screens that examine the contribution of every gene to a biological process. The directed nature of these experiments contrasts with traditional methods, in which random mutations are induced and the resulting mutants are screened for various phenotypes. The first genome-wide functional screens in Caenorhabditis elegans and Drosophila melanogaster have recently been published, and screens in human cells will soon follow. These high-throughput techniques promise the rapid annotation of genomes with high-quality information about the biological function of each gene.